Preparation method and application of carbon nanocage loaded indium oxide catalyst
By loading indium oxide materials on carbon nanocages, the coordination between photochemistry and photothermal effects is achieved, the problem of low light utilization efficiency of traditional photocatalysts is solved, the activity and stability of the catalyst are improved, and high-efficiency light under the entire solar spectrum is achieved- Chemical energy conversion, suitable for carbon dioxide hydrogenation gas to methanol reaction.
Patent Information
- Application Number
- CN202411132198.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Traditional photocatalysts have low light utilization efficiency and cannot effectively utilize the entire solar spectrum, resulting in insufficient efficiency in photochemical catalyzing of hydrogenation of carbon dioxide to produce methanol, and high photothermal catalytic reaction temperature, and poor catalyst activity and stability.
Using carbon nanocage-loaded indium oxide catalyst, the UV-band photochemical effect and visible-infrared band photothermal effect are achieved by combining the multi-stage pore structure of the carbon nanocage and the photochemical characteristics of the indium oxide material, and the synergy between the ultraviolet band photochemical effect and the visible-infrared band photothermal effect are improved, thereby improving the utilization efficiency and catalytic activity of light. .
It realizes efficient utilization of the entire solar spectrum, improves the activity and stability of the catalyst, promotes photo-chemical energy conversion, and is suitable for solar energy-driven carbon dioxide hydrogenation gas to methanol reaction under mild conditions.
Smart Images

Figure CN119236914A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of a carbon nano cage-loaded indium oxide catalyst. Background Art
[0002] Liquid sunlight methanol synthesis technology is of great significance for the development of clean energy and mitigation of the "greenhouse effect", and has become a research frontier in the fields of materials, catalysis and energy. Compared with gas energy, methanol is more stable, easy to store and transport, and is one of the best media for storing hydrogen; it can also be used as high-value-added chemicals and fuels such as low-carbon olefins and aromatics to promote the development of green and clean energy. The ideal photocatalytic carbon dioxide hydrogenation system to produce methanol is to use sunlight as the only energy to drive the reaction. However, traditional photochemical catalysts can usually only respond to ultraviolet and a small part of the visible light band. Limited by its low light utilization efficiency, the efficiency of photochemical catalytic carbon dioxide hydrogenation to produce methanol is still far lower than the actual application requirements.
[0003] Recently, researchers have proposed the idea of photothermal catalysis of carbon dioxide hydrogenation to produce methanol. By broadening the solar spectrum response range (part of the visible and infrared light bands), the photothermal effect of the catalyst is used to convert light energy into heat energy, thereby driving the catalytic reaction. This reaction pathway is expected to be driven by pure sunlight, thereby replacing traditional heat sources and reducing the use of fossil energy and carbon emissions. Professor Ozin's research group at the University of Toronto, Canada, reported a new type of "black indium oxide" photothermal catalyst, and its methanol catalytic activity and selectivity modification strategies have also emerged. However, the essence of photothermal catalysis is still thermal activation, and its reaction temperature is high, which is not conducive to the formation of methanol from a thermodynamic point of view (the production of methanol from carbon dioxide hydrogenation is an exothermic reaction), and the harsh conditions also affect the life of the catalyst. Therefore, photothermal catalysis of carbon dioxide hydrogenation to produce methanol is expected to be fully driven by sunlight, but it is still limited by the mismatch between thermodynamics and kinetics, and the activity, selectivity and stability of the catalyst are in urgent need of improvement.
[0004] The development of photothermal / photochemical synergistic catalytic systems and the efficient use of the entire solar spectrum provide a new path for building an efficient photochemical energy conversion system. Generally speaking, the photochemical effect mainly utilizes short-wavelength sunlight, while the photothermal effect mainly utilizes long-wavelength sunlight, but the same material system is often difficult to efficiently utilize at the same time.
[0005] In view of the above situation, it is necessary to develop a photothermal / photochemical synergistic catalyst that can efficiently utilize the entire solar spectrum, so as to achieve effective synergy of photochemical effects in the ultraviolet band and photothermal effects in the visible-infrared band, greatly improve the utilization efficiency of light, and achieve efficient photo-chemical energy conversion, thereby realizing the use of sunlight as the only energy to drive the catalytic hydrogenation of carbon dioxide to produce methanol. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a carbon nanocage-supported indium oxide catalyst and its application in catalytic carbon dioxide hydrogenation to methanol production. By selecting a carbon nanocage carrier with excellent photothermal performance, high specific surface area and multi-level pore structure and combining it with an indium oxide semiconductor material with good photochemical properties and excellent intrinsic catalytic performance, the prepared carbon nanocage-supported indium oxide catalyst has the advantages of excellent photothermal performance, efficient utilization of the entire spectrum and a high number of active sites. At the same time, the effective synergy of the photochemical effect in the ultraviolet band and the photothermal effect in the visible-infrared band can achieve efficient photo-chemical energy conversion, laying a foundation for catalytic carbon dioxide hydrogenation to methanol production under complete sunlight drive.
[0007] The first object of the present invention is to provide a method for preparing a carbon nanocage-supported indium oxide catalyst, comprising the following steps:
[0008] S1: dissolving the carbon nanocage and the indium salt compound in a solvent and mixing them evenly to obtain a mixed solution;
[0009] S2: adding an alkaline compound to the mixed solution for heating reaction to obtain carbon nanocage-loaded indium hydroxide powder;
[0010] S3: calcining the carbon nanocage-supported indium hydroxide powder in an inert atmosphere to obtain the carbon nanocage-supported indium oxide catalyst.
[0011] Furthermore, in step S1, the mass ratio of the carbon nanocage to the indium salt compound is 1:(5-10).
[0012] Furthermore, the indium salt compound in step S1 is selected from one or more of indium nitrate, indium chloride and indium sulfate.
[0013] Furthermore, the solvent in step S1 is deionized water or ethanol.
[0014] Furthermore, the alkaline compound in step S2 is ammonia water or sodium hydroxide.
[0015] Furthermore, in step S2, the heating temperature is 60-100° C., and the heating time is 10-30 min.
[0016] Furthermore, the gas of the inert atmosphere in step S3 is argon, the temperature of the inert atmosphere calcination is 200-400° C., and the time of the inert atmosphere calcination is 1-3 hours.
[0017] Furthermore, step S3 further includes a step of calcining in a hydrogen atmosphere.
[0018] Furthermore, the calcination temperature in the hydrogen atmosphere is 200-400° C., and the calcination time in the hydrogen atmosphere does not exceed 2 hours.
[0019] The second object of the present invention is to provide a carbon nanocage-loaded indium oxide catalyst prepared by the above preparation method.
[0020] Furthermore, the indium oxide is loaded on the surface of the carbon nanocage or between adjacent carbon nanocages.
[0021] Furthermore, the loading amount of the indium oxide is 20-40%.
[0022] Furthermore, the carbon nanocage-supported indium oxide catalyst has a reflectivity of 6-12% at a wavelength of 200-2300nm.
[0023] The third object of the present invention is to provide an application of a carbon nano cage-supported indium oxide catalyst in catalyzing the hydrogenation of carbon dioxide to produce methanol, the specific steps comprising:
[0024] The obtained carbon nanocage-loaded indium oxide catalyst is ultrasonically dispersed in ethanol and evenly drop-coated on glass fiber filter paper, and then transferred to a stainless steel stationary phase or mobile phase reactor, and carbon dioxide, hydrogen and nitrogen are introduced to react and generate methanol.
[0025] Furthermore, the reaction temperature is 280°C, the reaction pressure is 2-2.8 MPa, the reaction light wavelength is 300-2500 nm, and the reaction light intensity is 0-3 W·cm -2 .
[0026] In summary, compared with the prior art, the advantages of the present invention are:
[0027] 1. The present invention uses carbon nanocages as carriers, utilizing their good light absorption ability in the visible and infrared bands, combined with the strong absorption of indium oxide in the ultraviolet band, to achieve efficient utilization of the entire solar spectrum.
[0028] 2. The present invention utilizes the structural advantages of the multi-level pore structure and large specific surface area of carbon nanocages to improve the dispersion of indium oxide and increase the number of reactive sites, thereby enhancing the catalytic activity.
[0029] 3. The present invention utilizes the excellent photothermal conversion performance of carbon nanocages to make up for the insufficient photothermal activity of indium oxide. The two complement each other perfectly, thereby realizing photothermal / photochemical synergistic catalysis of carbon dioxide hydrogenation to produce methanol.
[0030] 4. The present invention adopts photothermal / photochemical synergistic catalysis as a new strategy for producing methanol from carbon dioxide hydrogenation, which is expected to achieve efficient conversion of solar energy into chemical energy under mild conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0032] Figure 1 The powder X-ray crystal diffraction pattern of catalyst a prepared in Example 1 of the present invention.
[0033] Figure 2 This is a transmission electron microscope image of catalyst a prepared in Example 1 of the present invention.
[0034] Figure 3 The UV-visible diffuse reflectance spectrum of catalyst a prepared in Example 1 of the present invention.
[0035] Figure 4 The powder X-ray crystal diffraction pattern of catalyst d prepared in Example 4 of the present invention.
[0036] Figure 5 This is a transmission electron microscope image of catalyst d prepared in Example 4 of the present invention.
[0037] Figure 6 The UV-visible diffuse reflectance spectrum of catalyst d prepared in Example 4 of the present invention.
[0038] Figure 7 The powder X-ray crystal diffraction pattern of catalyst e prepared in Example 5 of the present invention.
[0039] Figure 8 This is a transmission electron microscope image of catalyst e prepared in Example 5 of the present invention.
[0040] Fig. 9 This is the UV-visible diffuse reflectance spectrum of catalyst e prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0042] Example 1
[0043] This specific embodiment provides a preparation method of catalyst a (a carbon nanocage-supported indium oxide catalyst with a loading of 20% and annealed at 400° C. in an argon atmosphere for 3 h), and the specific steps are as follows:
[0044] Step (1): 20 mg of carbon nanocages and 100 mg of indium chloride were dissolved in 12 mL of deionized water, and the mixture was stirred thoroughly with a magnetic stirrer at a stirring rate of 300 rpm. Under stirring conditions, 5 mL of ammonia water, 15 mL of anhydrous ethanol and 4 mL of deionized water were added thereto, and stirring was continued for 15 min to obtain a mixed solution;
[0045] Step (2): the mixed solution was transferred into a round-bottom flask, the round-bottom flask was placed in an oil bath, the liquid surface of the mixed solution was immersed, the mixture was heated to 80°C in the oil bath for reaction for 30 minutes, and then naturally cooled to room temperature in the air, centrifuged and washed with deionized water for 3 times, and dried in a vacuum oven for 12 hours to obtain a powder material of carbon nanocage-loaded indium hydroxide;
[0046] Step (3): The dried carbon nanocage-loaded indium hydroxide powder material is subjected to high temperature annealing at 400° C. in an argon atmosphere for 3 h to obtain catalyst a.
[0047] The powder X-ray crystal diffraction pattern of catalyst a sample is as follows: Figure 1 As shown by Figure 1 It can be seen that the characteristic diffraction peaks of the sample completely correspond to the standard characteristic diffraction peaks of indium oxide PDF#06-0416 card, indicating that the sample did not undergo phase change or decomposition during the high-temperature annealing process and still maintained the crystalline phase of indium oxide. Figure 2 As shown by Figure 2 It can be seen that under the condition of annealing at 400℃ in argon atmosphere for 3h, it can be clearly observed that the carbon nanocage has a lighter contrast, while the indium oxide has a darker contrast. It is dispersed on the outer surface of the carbon nanocage and in the gaps between adjacent cages, with an average size of about 15nm. The UV-visible diffuse reflectance spectrum of catalyst a sample is shown in Figure 3 As shown by Figure 3 It can be seen that the reflectivity of the sample is 6-12% in the wavelength spectrum of 200-2300nm, indicating that the sample has a good light response in the entire spectrum.
[0048] Example 2
[0049] This specific embodiment provides a preparation method of catalyst b (30% loading, carbon nano cage-loaded indium oxide catalyst annealed at 400° C. in argon atmosphere for 2 h), and the specific steps are as follows:
[0050] Step (1): 20 mg of carbon nanocages and 150 mg of indium nitrate were dissolved in 12 mL of anhydrous ethanol, and the mixture was stirred thoroughly with a magnetic stirrer at a stirring rate of 300 rpm. Under stirring conditions, 5 mL of 1M NaOH solution, 5 ml of anhydrous ethanol and 14 ml of deionized water were added thereto, and stirring was continued for 15 min to obtain a mixed solution;
[0051] Step (2): the mixed solution was transferred to a round-bottom flask, the round-bottom flask was placed in an oil bath, the liquid surface of the mixed solution was immersed, the mixture was heated to 60°C in an oil bath for reaction for 20 minutes, and then naturally cooled to room temperature in air, centrifuged and washed with deionized water for 3 times, and dried in a vacuum oven for 12 hours to obtain a powder material of carbon nanocage-loaded indium hydroxide;
[0052] Step (3): The dried carbon nanocage-loaded indium hydroxide powder material is subjected to high temperature annealing at 400° C. in an argon atmosphere for 2 h to obtain catalyst b.
[0053] Example 3
[0054] This specific embodiment provides a preparation method of catalyst c (loading amount 40%, carbon nano cage-supported indium oxide catalyst annealed at 400° C. in argon atmosphere for 1 h), and the specific steps are as follows:
[0055] Step (1): 20 mg of carbon nanocages and 200 mg of indium sulfate were dissolved in 12 mL of anhydrous ethanol, and the mixture was stirred thoroughly with a magnetic stirrer at a stirring rate of 300 rpm. Under stirring conditions, 5 mL of ammonia water, 15 mL of anhydrous ethanol and 4 mL of deionized water were added thereto, and stirring was continued for 15 min to obtain a mixed solution;
[0056] Step (2): transferring the mixed solution into a round-bottom flask, placing the round-bottom flask in an oil bath pot, immersing the liquid surface of the mixed solution, heating to 100° C. in an oil bath for reaction for 10 min, then naturally cooling to room temperature in air, washing with deionized water three times after centrifugation, and drying in a vacuum oven for 12 h to obtain a powder material of carbon nanocage-loaded indium hydroxide;
[0057] Step (3): The dried carbon nanocage-loaded indium hydroxide powder material is subjected to high temperature annealing at 400° C. in an argon atmosphere for 1 h to obtain catalyst c.
[0058] Example 4
[0059] This specific embodiment provides a preparation method of catalyst d (loading amount is 20%, carbon nano cage supported indium oxide catalyst is annealed in argon atmosphere at 300°C for 3h and then annealed in hydrogen atmosphere at 200°C for 1h), the specific steps are as follows:
[0060] Step (1): 20 mg of carbon nanocages and 100 mg of indium nitrate were dissolved in 12 mL of deionized water, and the mixture was stirred thoroughly with a magnetic stirrer at a stirring rate of 300 rpm. Under stirring conditions, 5 mL of ammonia water, 15 mL of anhydrous ethanol and 4 mL of deionized water were added thereto, and stirring was continued for 15 min to obtain a mixed solution;
[0061] Step (2): the mixed solution was transferred into a round-bottom flask, the round-bottom flask was placed in an oil bath, the liquid surface of the mixed solution was immersed, the mixture was heated to 80°C in the oil bath for reaction for 30 minutes, and then naturally cooled to room temperature in the air, centrifuged and washed with deionized water for 3 times, and dried in a vacuum oven for 12 hours to obtain a powder material of carbon nanocage-loaded indium hydroxide;
[0062] Step (3): The dried carbon nanocage-loaded indium hydroxide powder material is subjected to high temperature annealing at 300° C. in an argon atmosphere for 3 h, and then annealed at 200° C. in a hydrogen atmosphere for 1 h, thereby obtaining catalyst d.
[0063] The X-ray crystal diffraction pattern of the catalyst d sample powder is as follows: Figure 4 As shown by Figure 4 It can be seen that the characteristic diffraction peaks of the sample completely correspond to the standard characteristic diffraction peaks of indium oxide PDF#06-0416 card, indicating that the sample did not undergo phase change or decomposition during the high-temperature annealing process and still maintained the crystalline phase of indium oxide. Figure 5 As shown by Figure 5 It can be seen that after annealing at 300℃ in argon atmosphere for 3h and then annealing at 200℃ in hydrogen atmosphere for 1h, it can be clearly observed that the carbon nanocage has a lighter contrast, while the indium oxide has a darker contrast. It is dispersed on the outer surface of the carbon nanocage and in the gaps between adjacent cages, with an average size of about 16nm. The UV-visible diffuse reflectance spectrum of catalyst d is shown in Figure 2. Figure 6 As shown by Figure 6 It can be seen that the reflectivity of the sample is 6-12% in the wavelength spectrum of 200-2300nm, indicating that the sample has a good light response in the entire spectrum.
[0064] Example 5
[0065] This specific embodiment provides a preparation method of catalyst e (loading amount is 20%, carbon nano cage loaded indium oxide catalyst is annealed at 200°C argon atmosphere for 3h and then annealed at 300°C hydrogen atmosphere for 2h), the specific steps are as follows:
[0066] Step (1): 20 mg of carbon nanocages and 100 mg of indium chloride were dissolved in 12 mL of deionized water, and the mixture was stirred thoroughly with a magnetic stirrer at a stirring rate of 300 rpm. Under stirring conditions, 5 mL of ammonia water, 15 mL of anhydrous ethanol and 4 mL of deionized water were added thereto, and stirring was continued for 15 min to obtain a mixed solution;
[0067] Step (2): the mixed solution was transferred into a round-bottom flask, the round-bottom flask was placed in an oil bath, the liquid surface of the mixed solution was immersed, the mixture was heated to 80°C in the oil bath for reaction for 30 minutes, and then naturally cooled to room temperature in the air, centrifuged and washed with deionized water for 3 times, and dried in a vacuum oven for 12 hours to obtain a powder material of carbon nanocage-loaded indium hydroxide;
[0068] Step (3): The dried carbon nanocage-loaded indium hydroxide powder material is subjected to high temperature annealing at 200° C. in an argon atmosphere for 3 h, and then annealed at 300° C. in a hydrogen atmosphere for 2 h, thereby obtaining catalyst e.
[0069] The X-ray crystal diffraction pattern of the catalyst e sample powder is as follows: Figure 7 As shown. Figure 7 It can be seen that the characteristic diffraction peaks of the sample completely correspond to the standard characteristic diffraction peaks of indium oxide PDF#06-0416 card, indicating that the sample did not undergo phase change or decomposition during the high-temperature annealing process and still maintained the crystalline phase of indium oxide. Figure 8 As shown. Figure 8 It can be seen that after annealing at 200℃ argon atmosphere for 3h and then annealing at 300℃ hydrogen atmosphere for 2h, it can be clearly observed that the carbon nanocage has a lighter contrast, while the indium oxide has a darker contrast. It is dispersed on the outer surface of the carbon nanocage and in the gaps between adjacent cages, with an average size of about 26nm. The UV-visible diffuse reflectance spectrum of catalyst e sample is shown in the figure below. Fig. 9 As shown. Fig. 9 It can be seen that the reflectivity of the sample is 6-12% in the wavelength spectrum of 200-2300nm, indicating that the sample has a good light response in the entire spectrum.
[0070] Test Example 1
[0071] Test of methanol catalytic performance of various catalysts under thermal catalysis
[0072] Catalyst a, catalyst b and catalyst c were ultrasonically dispersed in ethanol and evenly drop-coated on glass fiber filter paper, and then transferred to a stainless steel stationary phase reactor. The catalytic performance of carbon dioxide hydrogenation to methanol under thermal catalysis was tested under the conditions of reaction temperature of 280°C, ambient pressure of 2.0 MPa, and gas flow rate ratio of N2:CO2:H2=2:2:6. The methanol catalytic performance of each catalyst is shown in Table 1.
[0073] Table 1 Test of methanol catalytic performance of various catalysts under thermal catalysis
[0074]
[0075] As shown in Table 1, the methanol production rate of catalyst a is 218.9 μmol / gh, and the methanol selectivity is 48.7%; the methanol production rate of catalyst b is 210.0 μmol / gh, and the methanol selectivity is 38.5%; the methanol production rate of catalyst c is 373.4 μmol / gh, and the methanol selectivity is 34.7%. In general, the catalytic effect of catalyst a is the best.
[0076] Test Example 2
[0077] Test of methanol catalytic performance of various catalysts under light-assisted thermal catalysis
[0078] Catalyst a, catalyst d and catalyst e were ultrasonically dispersed in ethanol and evenly drop-coated on glass fiber filter paper. They were then transferred to a stainless steel mobile phase reactor and illuminated with a full-spectrum xenon lamp with a wavelength of 300-2500nm and an illumination intensity of 0.4W·cm -2 The catalytic performance of light-assisted thermal catalytic carbon dioxide hydrogenation to methanol was tested under the conditions of reaction temperature of 280°C, ambient pressure of 2.8 MPa, and gas flow rate ratio of N2:CO2:H2=2:2:6. The methanol catalytic performance of each catalyst is shown in Table 2.
[0079] Table 2 Test of methanol catalytic performance of various catalysts under light-assisted thermal catalysis
[0080]
[0081] As shown in Table 2, the methanol generation rate of catalyst a photo-assisted thermal catalysis is 1809.4 μmol / gh, and the methanol selectivity is 17.8%; the methanol generation rate of catalyst d photo-assisted thermal catalysis is 1780.2 μmol / gh, and the methanol selectivity is 17.4%; the methanol generation rate of catalyst e photo-assisted thermal catalysis is 1353.1 μmol / gh, and the methanol selectivity is 18.2%. In general, the catalytic effect of catalyst a photo-assisted thermal catalysis is the best.
[0082] Test Example 3
[0083] Test of methanol catalytic performance of various catalysts under photocatalysis
[0084] Catalyst a was ultrasonically dispersed in ethanol and evenly coated on glass fiber filter paper. It was then transferred to a stainless steel mobile phase reactor and illuminated with a full-spectrum xenon lamp with a wavelength of 300-2500nm and an illumination intensity of 2.75W·cm -2 The catalytic performance of photocatalytic carbon dioxide hydrogenation to methanol was tested under the conditions of ambient pressure of 2.8 MPa and gas flow rate ratio of N2:CO2:H2=2:2:6. The catalytic performance of methanol is shown in Table III.
[0085] Table 3 Test of methanol catalytic performance of catalysts under photocatalysis
[0086]
[0087] From Table 3, we can see that the methanol generation rate under photocatalysis is 1220.6 μmol / gh, and the methanol selectivity is 96%. Under pure photocatalytic conditions, both the methanol generation rate and the methanol selectivity reach a high level.
[0088] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a carbon nanocage-supported indium oxide catalyst, characterized in that: The following steps are involved: S1: dissolving the carbon nanocage and the indium salt compound in a solvent and mixing them evenly to obtain a mixed solution; S2: adding an alkaline compound to the mixed solution for heating reaction to obtain carbon nanocage-loaded indium hydroxide powder; S3: calcining the carbon nanocage-supported indium hydroxide powder in an inert atmosphere to obtain the carbon nanocage-supported indium oxide catalyst.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon nanocage to the indium salt compound in step S1 is 1:(5-10).
3. The preparation method according to claim 1, characterized in that: In step S3, the calcination temperature in the inert atmosphere is 200-400° C., and the calcination time in the inert atmosphere is 1-3 hours.
4. The preparation method according to claim 1, characterized in that: The step S3 further includes a step of calcining in a hydrogen atmosphere.
5. The preparation method according to claim 4, characterized in that: The calcination temperature in the hydrogen atmosphere is 200-400° C., and the calcination time in the hydrogen atmosphere does not exceed 2 hours.
6. The carbon nanocage-supported indium oxide catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. The carbon nanocage-supported indium oxide catalyst according to claim 6, characterized in that: The indium oxide is loaded on the surface of the carbon nanocage or between adjacent carbon nanocages.
8. The carbon nanocage-supported indium oxide catalyst according to claim 6, characterized in that: The loading amount of the indium oxide is 20-40%.
9. Use of the carbon nanocage-supported indium oxide catalyst according to any one of claims 6 to 8 in catalyzing the hydrogenation of carbon dioxide to produce methanol.
10. The use according to claim 9, characterized in that: The reaction conditions for preparing methanol by adding hydrogen to carbon dioxide include light irradiation, and the wavelength of the light is 300-2500nm.
Citation Information
Patent Citations
Method for producing hydrogen by direct photo-thermal synergistic catalysis of methanol
CN112973703A
Process for methanol synthesis using an indium oxide based catalyst
US20200048173A1
Supported indium oxide catalyst and process for methanol synthesis using the same
US20200061582A1
Noble metal promoted supported indium oxide catalyst for the hydrogenation of co2 to methanol and process using said catalyst
US20210322957A1
